A quick & easy guide to coming out - Russo, Kristin; Teixeira, Ravi (Linerence Press, an imprint of Oni-Lion Forge Publishing, 2024)
"Whether you're queer, trans, questioning, or anything in between, coming out to the folks in your life can be nerve-racking and stressful. Luckily, writer Kristin Russo (This is a Book for Parents of Gay Kids) and cartoonist Ravi Teixeira are here to guide you through the process, no matter where in your journey you are. From finding supportive resources, navigating awkward conversations, and embracing queer joy and community, this guide explores the twists and turns of coming out as every shade of LGBTQ+, helping you walk the path of sharing the truest you"--Back cover.